2011
DOI: 10.1007/s00467-011-1829-6
|View full text |Cite
|
Sign up to set email alerts
|

CKD-MBD after kidney transplantation

Abstract: Successful kidney transplantation corrects many of the metabolic abnormalities associated with chronic kidney disease (CKD); however, skeletal and cardiovascular morbidity remain prevalent in pediatric kidney transplant recipients and current recommendations from the Kidney Disease Improving Global Outcomes (KDIGO) working group suggest that bone disease—including turnover, mineralization, volume, linear growth, and strength—as well as cardiovascular disease be evaluated in all patients with CKD. Although few … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 96 publications
0
13
1
Order By: Relevance
“…The 1,25‐(OH) 2 vitamin D levels increase due to the normalization of graft function at post‐RTx period . However, in our study it was determined that 56% of the RTR and approximately half of the control subjects had overt 1,25‐(OH) 2 vitamin D deficiency.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…The 1,25‐(OH) 2 vitamin D levels increase due to the normalization of graft function at post‐RTx period . However, in our study it was determined that 56% of the RTR and approximately half of the control subjects had overt 1,25‐(OH) 2 vitamin D deficiency.…”
Section: Discussioncontrasting
confidence: 50%
“…Currently, BMD with DEXA method is the most commonly used diagnostic technique for evaluating post‐RTx osteoporosis . However, this technique has low reliability for the determination of BMD as it enables only two‐dimensional evaluation instead of volumetric measurement and is insufficient for demonstrating underlying abnormalities of bone histology .…”
mentioning
confidence: 99%
“…Accordingly, improvement in uremic CV disease following renal transplantation has been reported; however, data on improvement of bone disease are somewhat controversial [7,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“… 21 , 22 On the downside, a few studies demonstrated a 50% prevalence of adynamic bone disease in hypercalcemic, hyperparathyroid renal transplantation recipients on long-term calcimimetic therapy. 23 …”
Section: Discussionmentioning
confidence: 99%